Understanding the Effects of Education on Health: Evidence from China - Wei Huang (Institute for the Study of Labor (IZA), 2015)
Using a national representative sample in China from three largest on-going surveys, this study examines the effects of education on health among working-age population and explores the potential mechanisms. Using the exogenous variation in temporal and geographical impacts of Compulsory Schooling Laws (CSLs), it finds an additional year of schooling decreases 2-percentage points in reporting fair or poor health, 1-percentage points for underweight and 1.5-percentage points for smoking, and increases cognition by about 0.16 standard deviation. Further analysis also suggests that nutrition, income, cognition and peer effects are important channels in the education-health nexus, and all of these factors explain almost half of the education's impact. These suggest that CSLs have improved national health significantly in China and the findings help to explain the mixed findings in the literature.
Keywords: I12; I21; I28; 330; education; health; China